A poly(dimethylsiloxane) microfluidic sheet reversibly adhered on a glass plate for creation of emulsion droplets for droplet digital PCR. Issue 2 (20th October 2016) - Nakashoji, Yuta; Tanaka, Hironari; Tsukagoshi, Kazuhiko; Hashimoto, Masahiko
Abstract : A PDMS microfluidic chip with T‐junction channel geometry, two inlet reservoirs, and one outlet reservoir was reversibly adhered on a glass plate through the viscoelastic properties of PDMS. This formed a detachable microfluidic device for creation of water‐in‐oil emulsion droplets that were used as discrete reaction compartments for the droplet digital PCR. The PDMS/glass device could continuously produce monodisperse droplets without leakage of fluids using a vacuum‐driven autonomous micropumping method. This droplet preparation technique only required evacuation of air dissolved in the PDMS before loading of oil and aqueous phases into separate inlet reservoirs. Degassing of the PDMS chip at approximately 300 Pa for 1.5 h in a vacuum desiccator gave 40 000 droplets in 80 min, which corresponded to a generation frequency of up to nine droplets per second. Over multiple runs the droplet creation was very reproducible, and the size reproducibility of generated droplets (polydispersity of up to 4.1%) was comparable to that acquired using other microfluidic droplet preparation techniques. Because the PDMS chip can be peeled off the glass plate, blocked channels can easily be fixed when they arise, and this extends the lifetime of the chip. Single DNA molecules partitioned into the droplets were successfully amplified by PCR. In addition, the droplet digital PCR platform allowed absolute quantification of low copy numbers of target DNA, and was robust against instrumental variance.